Hourly Cooling Load Assessment Utilizing Three Different Methods for a Full Day - Khalaf, Feras Mutar; Sultan, Hussein S.; Alshara, Ahmed Kadhim (Basrah Journal for Engineering Sciences, 2025)
Human beings are facing an unprecedented rise in temperature rates not recorded for years. HVAC (heating, ventilation, and air conditioning) systems have been created and enhanced to solve this issue. Cooling load must be estimated with accepted methodologies before designing an efficient and effective air conditioning system. Companies, researchers, institutions, and others advise and develop many cooling load calculation methods. Each one of these methods has its advantages and disadvantages and may give a slightly different result for the same case. For each building, whether it was residential or commercial buildings, gyms, or shopping malls, before making the decision on (HVAC) systems to be used, both heating and cooling loads should be obtained as correctly as possible to minimize expenses as possible. Since the HVAC system consumes the most energy in an air-conditioned building, an accurate method of cooling load estimation is necessary. Consequently, an energy-efficient air conditioning system reduces greenhouse gas emissions into the atmosphere while also saving money on electricity. Two cases have been compared and studied, one in Dubai UAE, and the other in Baghdad Iraq. Three different methods, HAP, hand calculation method (CLTD/SCL/CLF), and MS-EXCEL E20 form sheet were used to compare the accuracy of the results for cooling load. Results of E20 and HAP are very close to each other with high accuracy for peak load, the big difference can be found between the CLTD method and the other two methods. The value of the maximum difference percentage was found between CLTD and E20 equals 3.28% and 7.96%, on the other hand, the lowest difference was equals to 0.3% and 1.51% between HAP and E20 results for Baghdad and Dubai respectively. Traditional and local materials came from local factories, used in buildings played a big effect on the results, which may not match those materials stated in the ASHRAE or CARRIER tables, which need to be considered in the results and calculation procedure. However, all methods have a percentage of difference but all results are within the accepted range and are applicable for practical cases. Of course, this percentage is minimal with some methods and maximum with others.